Syndrom bolestivého mĕchýre u intersticiální cystitidy: závislost mezi príznaky, endoskopickým nálezem, biopsií a lécbou - Zámecník, L; Hanus, T; Pavlík, I (Casopis lekaru ceskych, 2007)
BACKGROUND: Interstitial cystitis/Painful Bladder Syndrome (IC) is a chronic abacterial inflammatory disease of the bladder wall. It is accompanied by predominant neuropathic pain. Typical symptoms of IC include: suprapubic pain, bladder pain even between voiding, urgency, short intervals between micturition with frequency and nocturia. The objective of the study was to find a correlation between a symptom score and endoscopy together with histopathologic findings from the detrusor biopsy and a correlation between symptoms before and after the intravesical treatment. METHODS AND RESULTS: We have evaluated a group of 30 patients with newly diagnosed IC prospectively. These patients were in the group 1. Control group 2 consisted of 10 patients with asymptomatic bacteriuria. Group 3 consisted of 15 patients with no voiding symptoms. Validated questionnaire (O'Leary-Sant Symptom (ICSI) and Problem Index (ICPI) was used to objectify subjective symptoms. The diagnosis of IC was based on the clinical assessment of subjective symptoms, urodynamic results, endoscopy and histology. The efficacy of therapy was found statistically significant only in the intravesical therapy. In the patients with immunohistochemically identified increased numbers of mast cells per one microscopic field, the correlation with ICSI and ICPI score was statistically significant. CONCLUSIONS: Differences in symptom score in the patients before and after the treatment were found significantly higher after the intravesical (with heparin) treatment then after peroral therapy. Significant differences in the correlations of ICSI and ICPI score values with the histopathologic finding (i.e. number of mast cells) were found.
Keywords: cystoskopie; bolest; jehlová biopsie; Cystitis, Interstitial; Pain; Female; Adult; dospělí; močový měchýř; endoskopie; Cystoscopy; Humans; ženské pohlaví; Endoscopy; lidé; Urinary Bladder; Biopsy, Needle; intersticiální cystitida